The impact of KOCs' short video marketing on students' unplanned purchases of pre-loved footwear - Giang Nguyen Thi Phuong; Tan Thai Dong; Thao Nguyen Ngoc Phuong; An Nguyen Thi Ha; Duc Pham Ngoc; Truc Le Thi Thanh (Jurnal Ekonomi Perusahaan, 2025)
In the digital economy, impulsive shopping behavior among Vietnamese students is gaining attention, driven largely by the influence of short videos from Key Opinion Consumers (KOCs). This study explores how KOCs impact impulsive buying, especially for second-hand footwear, an affordable and unique item that frequently attracts students. The research examines the role of KOCs' short video content in shaping students' unplanned purchase decisions. A mixed-method approach was employed, beginning with semi-structured interviews to gauge initial insights, followed by a quantitative survey of 524 students in Ho Chi Minh City. After data refinement, 512 responses were analyzed using the PLS-SEM model in SMARTPLS-4 software. The study concludes that KOCs play a substantial role in driving impulsive purchases among Vietnamese youth in the digital era. These findings offer insights for financial management education and effective influencer marketing strategies within Vietnam’s growing digital consumer landscape.